High triglyceride to HDL cholesterol ratio is associated with increased coronary heart disease among White but not Black adults - Cesar Higgins Tejera; Jessica Minnier; Sergio Fazio; Monika M Safford; Lisandro D. Colantonio; Marguerite R Irvin; Virginia Howard; Neil A Zakai; Nathalie Pamir (Elsevier, 2021)
Objective: Black adults are less likely than White adults to present with adverse lipid profiles and more likely to present with low-grade inflammation. The impact of race on the association between atherogenic lipid profiles, inflammation, and coronary heart disease (CHD) is unknown. Methods: We evaluated the association between high levels (>50th percentile) of high-sensitivity C-reactive protein (hsCRP) and of triglycerides to high density lipoprotein ratio (TG/HDL-C) and CHD events by race in the REasons for Geographic and Racial Differences in Stroke (REGARDS) cohort with 30,239 Black and White participants aged 45 and older. Results: Participants with both high hsCRP and high TG/HDL-C had highest rates of CHD (HR 1.84; 95% CI: 1.48, 2.29 vs HR 1.52; 95% CI: 1.19, 1.94 in White vs Black participants respectively). Whereas isolated high hsCRP was associated with increased CHD risk in both races (HR 1.68; 95% CI: 1.31, 2.15 and HR 1.43; 95% CI: 1.13, 1.81 for White and Black participants respectively), isolated high TG/HDL was associated with increased CHD risk only in White participants (HR 1.44; 95% CI: 1.15, 1.79 vs HR 1.01; 95% CI: 0.74, 1.38). Further, the effects of high hsCRP and high TG/HDL-C were additive, with inflammation being the driving variable for the association in both races. Conclusion: In both races, higher inflammation combined with adverse lipid profile is associated with greater CHD risk. Therefore, inflammation increases CHD risk in both races whereas dyslipidemia alone is associated with a greater risk in White but not in Black adults. hsCRP testing should be a standard feature of CHD risk assessment, particularly in Black patients.